Belgische Malerei seit 1900. - Vanbeselaere, Walther; Hofmann, Werner (Wien : Museum des 20. Jahrhunderts, 1962)
Alechinsky, Pierre ; van Anderlecht, Engelbert ; Van den Berghe, Frits ; Bertrand, Gaston ; Bonnet, Anne ; de Braekeleer, Henri ; Burssens, Jan ; Camus, Gustave ; Cox, Jan ; Daeye, Hippolyte ; Delvaux, Paul ; Dudant, Roger ; Ensor, James ; Evenepoel, Henri ; Gentils, Vic ; Van Hoeydonck, Paul ; Khnopff, Fernand ; Landuyt, Octave ; Van Lint, Louis ; Maas, Paul ; Maes, Jacques ; Magritte, René ; Masereel, Frans ; Mendelson, Marc ; Mortier, Antoine ; Opsomer, Isidore ; Peire, Luc ; Permeke, Constant ; Ransy, Jan ; Rets, Jean ; Van Ruysselberghe, Theo ; de Saedeleer, Valérius ; Saverys, Albert ; Servranckx, Victor ; Slabbinck, Rik ; de Smet, Gustave ; Smits, Jakob ; Somville, roger ; Spilliaert, Léon ; Spilliaert, Léon ; Tytgat, Edgard ; van de Velde, Henry ; Vinck, Joseph ; Vogels, Guillaume ; Wyckaert, Maurice ; Van de Woestyne, Gustave ; Van de Woestyne, Maxime ; Wolvens, Henri Victor ; Wolvens, Henri Victor ; Wouters, Rik
Belgische Malerei seit 1900, Museum des 20. Jahrhunderts, Wien, 19. November bis 15. Dezember 1962
Duits
kunstcatalogus
Keywords: België